Doug makes the team - Krulik, Nancy E.; Peters, Matthew C.; Jinkins, Jim. (New York : Disney Press, 1998)
Doug tries out for the soccer team and becomes the mascot, but when Patti sprains her ankle, he goes in and wins the game.
"Jumbo Pictures."
"Original characters for 'The Funnies' developed by Jim Jinkins and Joe Aaron"--T.p. verso.
"Disney's Doug created by Jim Jinkins."
"Ages 7-9"-- P. [4] of cover.
Keywords: Soccer -- Fiction